P-284 Correlation between a new day 4 embryo scoring system and blastocyst development and pregnancy rate. (30th June 2022) - Martello, C; Andrade, G; Frantz, G; Pagnoncelli, N; Dutra, C; Rockenbach, M; Donatti, L; Frantz, N
Abstract: Study question: Does a new day 4 embryo scoring system predict blastocyst development and aneuploidies? Summary answer: The new day 4 embryo scoring system correlates with blastocyst development, blastocyst morphology, day of blastulation, and pregnancy rate. What is known already: A small number of studies propose different day 4 embryo grading systems. The majority of them report no differences in implantation and clinical pregnancy outcome between day 4 and blastocyst transfer. Moreover, only limited data exist on the association between day 4 grading systems, embryo development, and PGT-A results. In addition, none of the previous studies analyzed the totality of the different day 4 embryo morphology and their subsequent development. Study design, size, duration: This is a single-center retrospective analysis from June 2019 to August 2021 including 762 embryos from 129 cycles. Day 4 embryos were graded A to J considering A the best morphology and were classified into 1, 2, 3, or 4 categories (1 being the more advanced development). Categories were compared among them to assess blastocyst development and aneuploidy rate. Participants/materials, setting, methods: Data were obtained from medical records with a previously given consent. Patient characteristics such as age, body mass index (BMI), and anti-Mullerian hormone (AMH) were compared among the four categories using ANOVA with Multiple Comparisons. Blastocyst development, blastocyst morphology, day of blastulation, and pregnancy rate were compared among the categories using Chi-square contingency. All analyses considered a significant p-value of 0.05. Main results and the role of chance: Younger women presented significantly more category 1 of day 4 embryos when compared with the other categories (p < 0.0001). BMI and AMH were similar among the categories (p = 0.3063 and p = 0.2533, respectively). There was a high correlation between day 4 categories and PGT-A blastocyst development (p < 0.0001), blastocyst morphology (p < 0.0001), and day of blastulation (p < 0.0001). Also, there was a significant correlation between pregnancy rates and the four categories (p = 0.0192). No correlation was observed when aneuploidy rate and level of aneuploidy were analyzed (p = 0.3614 and p = 0.1490, respectively). Limitations, reasons for caution: The limited number of embryos analyzed is a limitation of the study, and additional data are being gathered. Multiple embryos of the same patients can be a cofounder of the study and more robust statistical analysis may overcome it. Wider implications of the findings: The new day 4 embryo score may be useful for embryo selection to PGT-A biopsy. Moreover, the proposed score may help to add valuable information to select the best embryos for transfer. Trial registration number: not applicable